Pelatihan Knowledge Management System Penanganan Anak Down Syndrome Bagi Pengurus Persatuan Orang Tua Anak dengan Down Syndrome Jawa Barat: Training on the Knowledge Management System for Handling Children with Down Syndrome for the Management of the Association of Parents of Children with Down Syndrome West Java - Mauluddin, Syahrul; Sidik, Rangga; Munandar, Dadang; Narimawati, Umi; Nursikuwagus, Agus (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Children with Down Syndrome face various physical challenges, such as muscle weakness, vulnerability to illnesses, and lower IQ levels compared to typical children. These conditions require special attention from parents, who must learn how to handle and care for children with Down Syndrome from an early stage. However, many parents struggle to access adequate information and knowledge about caring for their children. This community service program aims to implement a Knowledge Management System (KMS) as a solution for handling children with Down Syndrome within the Association of Parents of Children with Down Syndrome (POTADS) in West Java. The program involves training and mentoring for POTADS administrators. Based on the evaluation results, the administrators of POTADS West Java have successfully utilized the KMS.